2010
DOI: 10.1159/000301578
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Fungi Induce Nasal Polyp Epithelial Cell Activation and Toll-Like Receptor Expression

Abstract: Background: The nasal epithelium is the first barrier encountered by airborne allergens and is an active participant in airway inflammation. Fungi have been increasingly recognized as important pathogens in sinusitis and airway diseases. The aim of the study was to evaluate fungal protease activity during cytokine production in nasal polyp epithelial cells and to determine the expression of Toll-like receptor (TLR) mRNA by fungi. Methods: Nasal polyp epithelial cells were obtained from patients and stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…regulation of the innate and adaptive immune response. [17][18][19][20] The pattern of TLR expression has been studied in many different type of cells. TLR2 and TLR4 mRNA have been found to be expressed in the nasal epithelial cells and these 2 genes have been reported to be significantly higher in chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…regulation of the innate and adaptive immune response. [17][18][19][20] The pattern of TLR expression has been studied in many different type of cells. TLR2 and TLR4 mRNA have been found to be expressed in the nasal epithelial cells and these 2 genes have been reported to be significantly higher in chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, TLR4 was reported to contribute to airborne fungi-induced production of interleukin-8 and granulocyte-macrophage colony-stimulating factor in nasal polyp epithelial cells. 20 However, the effects of β-glucan on the productions of major airway mucins and the exact mechanisms related with TLRs have not been determined in human airway epithelial cells. Therefore, this study was conducted to determine whether β-glucan regulates the expressions of major airway mucin genes and to investigate the signaling pathway responsible for β-glucan-induced mucin production in human airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of chemical mediator production by BV was different depending on the kinds of allergen or stimulants. Although we cannot explain the exact cause of these discrepancies, these stimulants may activate nasal epithelial cells using different pathophysiologic mechanisms through receptors including G-protein-coupled receptors, toll-like receptors or protease-activated receptors or through various kinds of signal pathway [10,12,14].…”
Section: Discussionmentioning
confidence: 91%
“…Lipopolysaccharide (LPS; 10 μg/ml) was used as positive control. In our previous experiments with NPECs, maximal cytokine production was found at 50 μg/ml of Alternaria and 25 μg/ml of Aspergillus, DP and DF, the same concentration of these allergens were used currently [11,12]. After 24 h of incubation, the supernatants and epithelial cells were harvested and stored at -70°C until they were assayed.…”
Section: Npec Culture and Activation With Airborne Allergensmentioning
confidence: 99%
“…21,22) Several studies showed the associations that inflammatory responses by molds are mediated via TLR4. 23,24) However, it is not known whether interactions between TLR4 and mold have an impact on the development of allergic diseases, including AD.…”
Section: Introductionmentioning
confidence: 99%